Associations between daily positive communication and sexual desire and satisfaction: an approach utilizing traditional analyses and machine learning. - Leistner, Christine E.; Vowels, Laura M.; Vowels, Matthew J.; Mark, Kristen P. (Sexual & Relationship Therapy, 2024)
Communication is an important component of many healthy sexual and romantic relationships. Positive communication strategies including expressing fondness and affection, exchanging compliments, and disclosing information about oneself with a partner are associated with relationship and sexual satisfaction, but less is known about its association to sexual desire. Most of the current literature has used traditional statistical analyses that assume errors are normally distributed and that associations between variables are linear. Our study aimed to examine the ways daily levels of four positive communication strategies are associated with relationship satisfaction, sexual satisfaction, and sexual desire among 246 mixed sex couples (N = 492). We performed both traditional hierarchical linear modeling and machine learning to provide a complimentary view of results from the different data analytic techniques. Findings indicated that daily positive communication received from a partner was associated with all outcome variables of interest that day as well as for subsequent days for both partners in the couple. All positive communication strategies predicted daily levels of desire, sexual satisfaction, and relationship satisfaction for the individual and each had unique associations with partner outcomes. Unique nonlinear interactions were found using machine learning. Findings have implications for researchers and practitioners. LAY SUMMARY: We found that when a person reports receiving positive communication from their romantic partner (fondness, affection, compliments and intimate disclosure) on a given day, both partners have higher levels of desire and satisfaction on that day. Positive communication can be practiced by couples to enhance their sexual and relational lives.